Vol. 155 : Information and Measuring Equipment and Technologies (IME&T 2017): VIII International Scientific and Practical Conference, November 22-25, 2017, Tomsk, Russia; [proceedings]; MATEC Web of Conferences - Siemens E. Eduard; Mehtiyev A. D.; Syryamkin V. I. Vladimir Ivanovich; Yurchenko A. V. Aleksey Vasilievich (2018, 2018)
Title screen